Enhancing ESP Instruction through SPADA UNTIRTA: Pre-Service Teachers’ Beliefs and Practices in ICT Integration - Hamer, Welliam; Rohimajaya, Nur Azmi; Prabowo, Jumbuh (English Department - University of Sultan Ageng Tirtayasa, 2025)
This study investigates the beliefs and classroom practices of pre-service English teachers in integrating Information and Communication Technology (ICT) into English for Specific Purposes (ESP) instruction through SPADA UNTIRTA, a locally developed online learning platform in Indonesia. Employing a sequential explanatory mixed-methods design, the research combined quantitative data from 60 participants using a validated questionnaire and qualitative insights from interviews with 10 selected respondents. The findings reveal a strong belief among participants in the pedagogical value of ICT, particularly in fostering learner engagement, contextualizing ESP content, and supporting independent learning. However, the actual implementation of ICT in instructional practices remains limited. Barriers include insufficient digital literacy, lack of pedagogical training, inconsistent access to ICT tools, and underutilization of SPADA UNTIRTA due to technical and operational challenges. The study highlights a significant gap between positive perceptions and actual teaching practices, indicating the need for enhanced professional development and curriculum integration of ICT-based pedagogies. It concludes that effective ICT integration requires not only favorable teacher beliefs but also systemic support, including institutional policies, training programs, and adequate digital infrastructure. The study offers recommendations for teacher education institutions to reinforce the alignment between pedagogical beliefs and practice in the digital learning environment.